The direct synthesis of hydrogen peroxide from H(2) and O(2) using Pd–Ni/TiO(2) catalysts - Crole, David A. (Philos Trans A Math Phys Eng Sci, 2020)
The direct synthesis of hydrogen peroxide (H(2)O(2)) from molecular H(2) and O(2) offers an attractive, decentralized alternative to production compared to the current means of production, the anthraquinone process. Herein we evaluate the performance of a 0.5%Pd–4.5%Ni/TiO(2) catalyst in batch and flow reactor systems using water as a solvent at ambient temperature. These reaction conditions are considered challenging for the synthesis of high H(2)O(2) concentrations, with the use of sub-ambient temperatures and alcohol co-solvents typical. Catalytic activity was observed to be stable to prolonged use in multiple batch experiments or in a flow system, with selectivities towards H(2)O(2) of 97% and 85%, respectively. This study was carried out in the absence of halide or acid additives that are typically used to inhibit sequential H(2)O(2) degradation reactions showing that this Pd–Ni catalyst has the potential to produce H(2)O(2) selectively. This article is part of a discussion meeting issue ‘Science to enable the circular economy’.